Theoretical Advances and Applications of Fuzzy Logic and Soft Computing - Castillo, Oscar; Melin, Patricia; Montiel Ross, Oscar; Sepúlveda Cruz, Roberto; Pedrycz, Witold (Advances in Intelligent and Soft Computing,, 2007)
This book comprises a selection of papers from the IFSA 2007 World Congress on theoretical advances and applications of fuzzy logic and soft computing. These papers were selected from over 400 submissions and constitute an important contribution to the theory and applications of fuzzy logic and soft computing methodologies. Soft Computing consists of several computing paradigms, including fuzzy logic, neural networks, genetic algorithms, and other techniques, which can be used to produce powerful intelligent systems for solving real-world problems. Applications range from pattern recognition to intelligent control and sow the advantages of using soft computing theory and methods. The papers of IFSA 2007 also make a contribution to this goal.